A Facility-Based Survey Of Cervical Cancer Prevention And Control Programs In Sub-Saharan Africa By Serra Lem Asangbeh, Graduate School For Cellular And Biomedical Sciences (Gcb) University Of Bern And Swiss Tropical And Public Health Institute (Swiss Tph) - Asangbeh-Kerman, Serra Lem (My University, 2023)
The preliminary results from a facility-based survey of cervical cancer prevention and control programs in Sub-Saharan Africa are presented. Main findings: HPV vaccination is available in less than half of the participating sites; funding support for cervical screening is rare; diagnostic and treatment services are mostly centralized (women often referred for these services off-site); cost is a barrier to diagnosis and treatment in most sites; data collection systems are available for HIV but rare for CC prevention; and across the cascade, data availability greatly reduces from screening to follow-up of treated women and women initially screened negative.
FUNDING These activities are part of the project: Cervical Cancer Prevention and Care Cascade for women living with HIV in sub-Saharan Africa, that has received support from the Swiss Agency for Development and Cooperation; grant Advancing Cervical Cancer Screening in HIV-positive women (ACCHIVe) —The Cervical Cancer Prevention and Care Cascade (Award number: IZP8Z0_180245). The research is also supported by the Eunice Kennedy Shriver National Institute Of Child Health & Human Development (NICHD), National Institute Of Diabetes And Digestive And Kidney Diseases (NIDDK), National Heart, Lung, And Blood Institute (NHLBI), National Institute On Alcohol Abuse And Alcoholism (NIAAA), Fogarty International Center (FIC), National Cancer Institute (NCI), and by the National Institute of Allergy and Infectious Diseases of the National Institutes of Health under Award Number U01AI069924. We acknowledge the funding from the European Union’s Horizon 2020 research and innovation programme under the Marie Skodowska-Curie grant agreement No 801076 and support from the Federal Commission for Scholarships for Foreign Students for the Swiss Government Excellence Scholarship (ESKAS No. 2019.0741). The content is solely the responsibility of the authors and does not necessarily represent the official views of the funders.
Keywords: HIV; sub-Saharan Africa; cervical cancer prevention